Adaptation of Anopheles Vectors to Anthropogenic Malaria-Associated Rubber Plantations and Indoor Residual Spraying: Establishing Population Dynamics and Insecticide Susceptibility - Suntorn Pimnon; Adisak Bhumiratana (Canadian Journal of Infectious Diseases and Medical Microbiology)
Anthropogenic activity such as the establishment of Anopheles-infested rubber plantations can influence local malaria transmission dynamics to which the population dynamics and insecticide susceptibility of local Anopheles vectors are related. Using human landing catch collections at a house protected by indoor residual spraying (IRS), the periodic assessment of species composition, abundance, and blood-feeding behaviors was done in pre-IRS, during IRS, and post-IRS at 3, 6, and 12 months in a malaria-associated rubber plantation (MRP) ecotope of the Bo Rai district, Trat Province, Thailand, after malaria outbreak occurred. The study MRP ecotope elicited the population ratio (pi) of Anopheles vectors: An. campestris (0.747), An. dirus (0.168), An. minimus (0.037), An. barbirostris (0.027), and An. pseudowillmori (0.002), and of An. jamesii nonvector (0.019). Among these, two predominant An. campestris and An. dirus night-biters were then used in the susceptibility test against 0.05% deltamethrin (DEL) and 0.09% bifenthrin (BT) insecticides currently used in IRS. An. campestris, a suspected vector of Plasmodium vivax, had a tendency to appear throughout the study and behaved both exophagy and endophagy. It was highly susceptible to BT, showing 95.0% mortality (95% CI, 79.1–100) while decreasing sensitivity of 87.2% (95% CI, 78.4–95.9) to DEL. An. dirus, a primary vector of Plasmodium falciparum, had a tendency to feed outdoors rather than indoors. Significant differences in the abundance (mean density and human landing rate) were observed at pre-IRS (P<0.001  and  P=0.046), and similarly, during IRS (P=0.001  and  P=0.037). It was highly susceptible to DEL and BT, showing 100% mortality rate. Evidently, the study MRP ecotope contributed receptive environment to favor the abundant local Anopheles vectors and their outdoor biting preference. This can pose the risk for residual malaria parasite transmission in Anopheles vectors even though the house is protected by IRS.